Access to menstrual hygiene products through incentivised, community-based, peer-led sexual and reproductive health services before and during the COVID-19 pandemic: findings from the Yathu Yathu trial - Hensen B; Gondwe M; Phiri M; Schaap A; Simuyaba M; Floyd S; Mwenge L; Sigande L; Shanaube K; Simwinga M; Fidler S; Hayes R; et al. (BMC, 2022)
Abstract Background Access to affordable and effective menstrual hygiene products (MHP) is critical to the menstrual health of adolescent girls and young women (AGYW). In this mixed-methods analysis, we use data from a programme delivering comprehensive sexual and reproductive health (SRH) services to describe access to MHP and how COVID-19-related closures affected access to MHP; we use qualitative data to understand AGYW's experience accessing products during the study. Methods Between September 2019-January 2021, we used data routinely collected from ten Yathu Yathu hubs offering community-based, peer-led SRH services to adolescents and young people aged 15-24. Hubs offered free MHP (primarily disposable pads) as a service. To incentivise service access, a "loyalty" card system was embedded within Yathu Yathu, allowing individuals to gain points for services accessed and redeem rewards using these points. Branded pads, tampons and reusable pads were among available rewards. We describe access to service pads and to reward MHP, and use logistic regression to investigate factors associated with accessing pads and reward products before (Sept 2019-March 2020) and after (July 2020-Jan 2021) COVID-19-related closures. Focus group discussions explored accessibility of offering MHP through hubs. Results Between September 2019-January 2021, 6374 AGYW made 34,116 hub visits to access an SRH service and/or redeem a reward. At 30% of these visits, AGYW accessed any MHP. Before COVID19-closures, an average of 17% of monthly visits were for freely-available disposable pads compared to 34% after hubs reopened (p < 0.001). Results were similar for reward visits. Overall, 63% of 6374 AGYW collected pads as a service at least once. Prior to COVID19-closures, AGYW aged 18-24 were more likely to access service pads than adolescents (15-17-years). After reopening, access was lower among older AGYW. Prior to hub closures, uptake of reward MHP was higher among AGYW with some secondary education but not after reopening. Discussions revealed that, for adolescents aged 15-19, COVID-19-related hub closures required reverting to using ineffective materials to manage menstruation. Conclusion Availability of MHP through Yathu Yathu provided a large number of AGYW with access to these products. Hubs seemed particularly important for adolescent girls. Community-based, peer-led hubs should be considered as spaces to provide AGYW access to affordable and effective MHP.